(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The representation of Scheduled Caste (SC) women in political arenas remains a critical issue in India, particularly in the state of Telangana. This study examines the role of political parties in enhancing the political representation of SC women in Telangana. By analyzing the strategies and initiatives undertaken by key political parties, the research aims to identify the factors that contribute to increased political participation and representation of SC women. The study employs a mixed-methods approach, combining qualitative interviews with SC women politicians and party leaders with quantitative data analysis of electoral outcomes and party policies. Key findings indicate that while quota systems and reservation policies have provided a foundational platform for SC women, the success of these measures is significantly influenced by the active engagement and support of political parties. Furthermore, the research highlights the importance of political mobilization, training, and capacity-building programs initiated by parties to empower SC women. Despite these efforts, numerous challenges persist, including socio-cultural barriers and intra-party dynamics. The study concludes with recommendations for political parties and policymakers to create a more inclusive political environment for SC women in Telangana.